The application of genetic algorithms to civil engineering optimisation problems - O'Dwyer, Dermot W. (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2001)
Genetic algorithms are optimisation algorithms that mimic the mechanisms of natural selection. This thesis is concerned with the theoretical development of genetic algorithms and with their successful application to civil engineering optimisation problems. This thesis can be subdivided into two sections. The first deals with the theoretical behaviour of genetic algorithms and the second deals with their application to civil engineering optimisation. The existing basis of the genetic algorithm rests on the schema theorem and the building-block hypothesis. Theoretical work presented in this thesis develops the schema theorem to include the effects of crossover and proves the building-block hypothesis. The new theoretical work presented on the schema theorem is related to existing fundamental theory in the field of population genetics.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin